THE ROLE OF GENDER IN VIDEO GAME USAGE, PREFERENCE, AND BEHAVIOR IN SURABAYA - Edwin Reinaldy Aditya Winata (Perpustakaan Universitas Surabaya, 2018)
This study aims to identify and analyze the differences of Behavior and describe the Usage and Preference toward Video Game between Male and Female gamers in Surabaya. The Video Game mentioned covers all electronic games, independent of their platform (computer, consoles, arcades, handheld, smartphone, etc.). The data used in this research gathered through direct offline physical Questionnaire which was adopted from Phan. et.al. (2012). Using Non-probability purposive sampling technique, sample of this research consisted of 200 respondents, composed from 100 Male and 100 Female respondents whose age is 17 years old or above, domiciled Surabaya, and routinely plays video game for at least two hours in a week. Further data analysis was analyzed by SPSS 23.0. Result of this study found that there is significant difference in behavior between male and female video gamers and describe each gender preferences toward genres and gaming device,also the usage of the video game.